A radiation tolerant laser-induced fluorescence detection system for a potential Europa Lander mission. (September 2021) - Oborny, Nathan J.; Kehl, Florian; Cretu, Vlad; Noell, Aaron C.; Willis, Peter A.
Abstract: Analytical techniques commonly implemented for in situ organic analysis on space missions lack the sensitivity or specificity necessary to definitively characterize key markers of current or past life, such as amino acids. To this end, our group has developed an analytical method for amino acid analysis at low parts-per-billion levels, utilizing capillary electrophoresis coupled to laser-induced fluorescence detection. Europa has been identified as a particularly appealing target for life detection, but its intense radiation environment presents additional challenges for instrument development and qualification. Here, we present work toward the development of a flight qualifiable laser-induced fluorescence detection system that could be implemented on potential future missions to the Jovian system which could experience total ionizing dose exposures of up to 300 krad. Our results show that a gallium nitride based laser diode and micro-photomultiplier based system can meet our system performance requirements under radiation conditions expected for a potential Europa Lander mission. Highlights: Laser-induced fluorescence detection coupled to a bioanalytical method such as capillary electrophoresis can provide extreme sensitivity for life detection missions to ocean worlds. Many such ocean world environments, such as the surface of Europa, have high levels of radiation that can negatively affect elements of a fluorescence detection system. The performance of commercially available lasers and photomultiplier tubes were evaluated both for mission survivability and operation while under irradiation. Under Europa analog test conditions, commercially available laser diodes and photomultiplier tubes meet performance requirements for 1 nM amino acid detection.